(untitled) (Fisioterapia e Pesquisa, 2005)
Physical therapy training in universities is usually focussed on rehabilitation processes developed in second and third health-attention levels; the approach to health problems is generally restricted to biological aspects. Based on the experience of a university extension project called Physical Therapy in the Community, this paper presents a qualitative analysis of that experience to assess its potential contribution to physiotherapists training. It became evident that the opportunity of providing physical therapy at first-level health services during school years may give the student a better perception of both human illness and professional intervention, thus enabling a more adjusted performance and more humanized relationships.